1998
DOI: 10.1128/aac.42.10.2722
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in the BALB/c Mouse: A Comparison of the Efficacy of a Nonionic Surfactant Formulation of Sodium Stibogluconate with Those of Three Proprietary Formulations of Amphotericin B

Abstract: In this study, treatment efficacies of a nonionic surfactant vesicle formulation of sodium stibogluconate (SSG-NIV) and of several formulations of amphotericin B were compared in a murine model of visceral leishmaniasis. Treatment with multiple doses of AmBisome, Abelcet, and Amphocil (total dose, 12.5 mg of amphotericin B/kg of body weight) resulted in a significant suppression of parasite burdens in liver (P < 0.0005) and spleen (P < 0.0005) compared with those of controls, with Abelcet having the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 11 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…It was also observed that the BUN and creatinine levels were not signicantly elevated, which in turn reected that the formulations of both types were not nephrotoxic at that particular dose regimen. The in vivo antileishmanial potency of the free AmB and both types of nanoformulations were evaluated on a chronic VL infected mice model according to Mullen et al 40 It was observed from Table 5 that the mannose modied AmB-loaded PLGA-OSM nanoparticles exerted superior activity over free AmB as well as over AmB-loaded nanoparticles. This was might be due to the mannose modication of the nanoformulation, which could easily be taken up by the macrophages, as is already evident from the ex vivo macrophage uptake study.…”
Section: Discussionmentioning
confidence: 99%
“…It was also observed that the BUN and creatinine levels were not signicantly elevated, which in turn reected that the formulations of both types were not nephrotoxic at that particular dose regimen. The in vivo antileishmanial potency of the free AmB and both types of nanoformulations were evaluated on a chronic VL infected mice model according to Mullen et al 40 It was observed from Table 5 that the mannose modied AmB-loaded PLGA-OSM nanoparticles exerted superior activity over free AmB as well as over AmB-loaded nanoparticles. This was might be due to the mannose modication of the nanoformulation, which could easily be taken up by the macrophages, as is already evident from the ex vivo macrophage uptake study.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable efficacy to ABLC even with lower AmBi tissue concentrations Higher concentrations in lung, liver and spleen as compared to AmBi [32,55,56] Targeting of liposomes to fungal infection sites in tissues as well as uptake by macrophages Uptake by macrophages [28] Toxicity and efficacy Lung infections Efficacy without nephrotoxicity at 5-20 mg ⁄ kg Efficacy without nephrotoxicity at 5 mg ⁄ kg; nephrotoxicity and decreased efficacy at 15 mg ⁄ kg [4,32] High-dose treatments Highest tolerated doses in infected animals = 30-50 mg ⁄ kg Highest tolerated doses in infected animals = 12-15 mg ⁄ kg [34,36,41,42,49,[52][53][54] Prophylaxis Localisation in cells and tissues Lung epithelial lining fluid; macrophages of spleen and liver; renal tubular epithelium of kidneys Pulmonary alveolar macrophages; peripheral monocytes [60] Concentration and retention in tissues Concentration ⁄ g tissue: Concentration ⁄ g tissue: [ [5,6]. ABLC is composed of ribbon-like structures with particle sizes between 1600 nm and 11 000 nm and a 1:1 molar ratio of AMB ⁄ phospholipid (dimyristoyl phosphatidylcholine and dimyristoyl phosphatidylglycerol mixture) [7].…”
mentioning
confidence: 99%
“…At 12 wk, when chronic LD infection was well established, animals were treated with CSA. In chronic infection, mice spleen and bone marrow burdens tended to be higher, and liver burdens tended to be lower, as compared with the acute‐infection model, and the most obvious difference was the greater hepatosplenomegaly typical of VL 14. Our data clearly demonstrates almost complete clearance of parasites from the spleen (99.1%±1.07), liver (99.8%±0.92) and bone marrow (98.2%±2.7) in the chronic infected model also (Fig.…”
Section: Resultsmentioning
confidence: 92%